Ezrin Ser66 phosphorylation regulates invasion and metastasis of esophageal squamous cell carcinoma cells by mediating filopodia formation. (July 2017) - Li, Li-Yan; Xie, Ying-Hua; Xie, Yang-Min; Liao, Lian-Di; Xu, Xiu-E; Zhang, Qiang; Zeng, Fa-Min; Tao, Li-Hua; Xie, Wen-Ming; Xie, Jian-Jun; Xu, Li-Yan; Li, En-Min
Abstract: Background: Ezrin, links the plasma membrane to the actin cytoskeleton, and plays an important role in the development and progression of human esophageal squamous cell carcinoma (ESCC). However, the roles of ezrin S66 phosphorylation in tumorigenesis of ESCC remain unclear. Methods: Distribution of ezrin in membrane and cytosol fractions was examined by analysis of detergent-soluble/-insoluble fractions and cytosol/membrane fractionation. Both immunofluorescence and live imaging were used to explore the role of ezrin S66 phosphorylation in the behavior of ezrin and actin in cell filopodia. Cell proliferation, migration and invasion of ESCC cells were investigated by proliferation and migration assays, respectively. Tumorigenesis, local invasion and metastasis were assessed in a nude mouse model of regional lymph node metastasis. Results: Ezrin S66 phosphorylation enhanced the recruitment of ezrin to the membrane in ESCC cells. Additionally, non-phosphorylatable ezrin (S66A) significantly prevented filopodia formation, as well as caused a reduction in the number, length and lifetime of filopodia. Moreover, functional experiments revealed that expression of non-phosphorylatable ezrin (S66A) markedly suppressed migration and invasion but not proliferation of ESCC cells in vitro, and attenuated local invasion and regional lymph node metastasis, but not primary tumor growth of ESCC cells in vivo . Conclusion: Ezrin S66 phosphorylation enhances filopodia formation, contributing to the regulation of invasion and metastasis of esophageal squamous cell carcinoma cells.